Menggali Sisi Positif Kebudayaan Lokal Tari Umbul dalam Menanamkan Nilai Cinta Tanah Air pada Siswa Sekolah Dasar - Yuniawati, Selin; Saputra, Yudha Munajat; Kurnia, Dadang (Jurnal Pena Ilmiah, 2021)
Umbul dance is a culture that grows and develops in society, the research to explore positive values in the Umbul dance, this study uses qualitative methods with an ethnographic research design, data collection by interview, observation and documentation techniques. The results showed that artists understand the values of the Umbul dance including 1) the value of cooperation, 2) the mutual cooperation, 3) the value love of peace, 4) the patriotism.The form of patriotism in the banner dance for elementary school is known from the indicators the meaning and performance of the Umbul dance. Students assume that the Umbul dance is a culture that must be studied with usefulness and interest in learning it, the management and preservation system of the Umbul dance involves the role of the community, artists and the government are fully responsible for the process of managing and preserving culture.